STABILITAS DAYA DUKUNG LATERAL STRUKTUR KEPALA JEMBATAN DI TANAH LUNAK - Dhiya Safira; Putera Agung Maha Agung (Politeknik Negeri Jakarta, 2021)
Pile is a deep foundation types of system always used to support a bridge abutment in a highway line. Pile foundation as one part of the sub-structure system can retain and transfer all loads from the upper structure. According to government standard regulation, a configuration of pile foundation must be selected and serve all external lateral loads in safety limits according to government standard regulation, including static and dynamic loads. This study evaluates the lateral stability of bridge abutment at the Indrapura Kisaran Toll Road section 2 at STA. 153 + 509, which designed using prestressed round pile foundations. Broms solution is a selected method to evaluate the lateral stability of a single and or group of pile foundations embedded in sand or sandy layers. From some design calculations, a configuration of 40 piles with a diameter of 50 cm shows adequately strong to resist all the lateral forces at the field. Keywords: Foundation, Piles, Sand.